Rekonstruksi Konsep Psikoseksual Sigmund Freud; Satu Tinjauan Islamisasi: Reconstructing Sigmund Freud's Psychosexual Concept: An Islamic Perspective - Husna Hisaba Kholid; Rudi Suherman; Fauzan Dhiyaurrahman (Indonesian Journal of Islamization Studies, 2023)
Psychosexual theory by Sigmund Freud has significantly influenced contemporary understanding of human personality. Freud postulated that neurotic mental disorders in humans are greatly influenced by their early childhood sexual experiences. While this theory has exerted substantial influence, it is not without its methodological shortcomings. Moreover, Muslim psychologists have identified a fundamental clash between the Freudian worldview and Islamic perspectives, deeming psychosexual theory incongruent with Islamic principles. Therefore, this paper aims to undertake a reconstruction of Freud's Psychosexual theory through an Islamic worldview lens. This study primarily relies on library research, with primary data sources comprising Sigmund Freud's original works and secondary data sources consisting of relevant books that strengthen arguments and supplement research data. Data analysis employs content analysis. The findings of this study reveal epistemological and worldview issues within psychosexual theory that are incongruent with Islamic perspectives. Thus, the process of Islamization of this theory becomes a necessity to remove elements conflicting with Islamic worldviews